Pengaruh Staffing dan Beban Kerja Terhadap Prestasi Kerja Karyawan di Pabrik Gula Djombang Baru - Ahsana Nadiyya Amany (BIMA : Journal of Business and Innovation Management, 2020)
The purpose of this analyze the effect of staffing and workload toward employee work performance at Sugar Factory of Djombang Baru. This type of research is associative description and sample collection techniques are purposive side techniques with a total sample of 122 employees of Sugar Factory in Djombang Baru. Data collection techniques using observation, interviews, questionnaires and documentation. Data analysis techniques using multiple linier regression. The results of this study indicate that, 1) Staffing has a partially significant effect on the work performance Djombang Baru Sugar Factory employees, 2) Workload has partially significant effect on the work performance Djombang Baru Sugar Factory employees and, 3) Staffing and workload simultaneously affects work performance of Djombang Baru Sugar Factory employees.